2021
DOI: 10.3390/cells10113113
|View full text |Cite
|
Sign up to set email alerts
|

RALBP1 in Oxidative Stress and Mitochondrial Dysfunction in Alzheimer’s Disease

Abstract: The purpose of our study is to understand the role of the RALBP1 gene in oxidative stress (OS), mitochondrial dysfunction and cognition in Alzheimer’s disease (AD) pathogenesis. The RALPB1 gene encodes the 76 kDa protein RLIP76 (Rlip). Rlip functions as a stress-responsive/protective transporter of glutathione conjugates (GS-E) and xenobiotic toxins. We hypothesized that Rlip may play an important role in maintaining cognitive function. The aim of this study is to determine whether Rlip deficiency in mice is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Overall, Rlip has several structural and functional domains related to oxidative stress and mitochondrial function that maintains cellular homeostasis, and a reduction of Rlip induces oxidative stress and mitochondrial dysfunction in neurodegenerative diseases such as AD. Our initial studies revealed that a partial reduction of Rlip induced oxidative stress and mitochondrial damage in AD [ 14 ]. However, further research is still needed in order to determine the precise domain structural involvement in oxidative stress/mitochondrial function in AD.…”
Section: Rlip Structure and Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, Rlip has several structural and functional domains related to oxidative stress and mitochondrial function that maintains cellular homeostasis, and a reduction of Rlip induces oxidative stress and mitochondrial dysfunction in neurodegenerative diseases such as AD. Our initial studies revealed that a partial reduction of Rlip induced oxidative stress and mitochondrial damage in AD [ 14 ]. However, further research is still needed in order to determine the precise domain structural involvement in oxidative stress/mitochondrial function in AD.…”
Section: Rlip Structure and Functionmentioning
confidence: 99%
“…Our recent findings show that heterozygous Rlip KO (Rlip +/− ) mice have significant increases in the dentate gyrus and hippocampus expression of Drp1 and Fis1, genes involved with mitochondrial fission, and decreased expression of the mitofusin MFN1 [ 14 ]. Electron microscopy images of hippocampal and cortical cells in Rlip +/− mice showed a larger number of smaller mitochondrial relative to controls with wild-type Rlip, indicating mitochondrial fragmentation [ 14 ]. Consistently, the activity of glutathione peroxidase, a mitochondrial antioxidant enzyme, decreased in the Rlip +/− mice, which also indicates a loss of mitochondrial function [ 14 ].…”
Section: Energy Production: Rlip In Mitochondrial Biogenesismentioning
confidence: 99%
See 3 more Smart Citations